Quantification of autoantibodies using a luminescent profiling method in autoimmune interstitial lung disease - Burbelo, Peter D.; Huapaya, Julio A.; Khavandgar, Zohreh; Beach, Margaret; Pinal-Fernandez, Iago; Mammen, Andrew L.; Chiorini, John A.; Noroozi Farhadi, Payam; Miller, Frederick W.; Schiffenbauer, Adam; Sarkar, Kakali; Warner, Blake M.; et al. (Frontiers in Immunology, 2024)
Autoantibodies are important for the diagnosis of autoimmune interstitial lung disease (ILD). Standard immunoassays have limitations, including their qualitative nature and/or a narrow dynamic range of detection, hindering the usefulness of autoantibodies as biomarkers of disease activity. Here, the luciferase immunoprecipitation system (LIPS) was evaluated for measuring myositis-specific and other lung-related autoantibodies in 25 subjects with idiopathic inflammatory myopathies (IIM), 26 with Sjögren’s disease (SjD), and 10 healthy volunteers. LIPS detected a broad dynamic range of autoantibodies, to MDA5, Jo-1, PL12, KS, U1-70K, and Ro52, and matched seropositivity status with established immunoassays. Robust anti-MDA5 autoantibodies in four IIM-ILD patients had a median value of 1,134,000 LU (IQR 473,000-2,317,000), which was 500 times higher than in 21 seronegative IIM patients. Markedly elevated anti-Jo-1 autoantibodies in five IIM-ILD patients demonstrated a median value of 1,177,000 LU (IQR: 604,000-2,520,000), which was 1000-fold higher than in seronegative patients. Robust anti-Ro52 and other anti-tRNA-synthetase autoantibodies were detected in a subset of IIM-ILD subjects. In SjD, only anti-U1-70K and KS autoantibodies were identified in ILD patients with a prevalence of 30% and 20%, respectively. In longitudinal samples of five IIM-ILD patients, anti-Jo-1 autoantibody levels paralleled clinical improvement of lung function. LIPS can accurately quantify autoantibody levels as biomarkers for treatment response in patients with autoimmune ILD.